2020
DOI: 10.1101/2020.05.21.109751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Membrane bending by protein phase separation

Abstract: Membrane bending is a ubiquitous cellular process that is required for membrane traffic, cell motility, organelle biogenesis, and cell division. Proteins that bind to membranes using specific structural features, such as wedge-like amphipathic helices and crescentshaped scaffolds, are thought to be the primary drivers of membrane bending. However, many membrane-binding proteins have substantial regions of intrinsic disorder, which lack a stable three-dimensional structure. Interestingly, many of these disorder… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
4
13
0
Order By: Relevance
“…Note that W is a scalar multiple of the total elastic bending energy of the membrane and h ( α ) is a scalar multiple of the mean curvature at the corresponding points on the membrane. The boundary conditions used for the original unknowns are: The boundary conditions for the corresponding sensitivities are all set to be zero. Our choices for the input parameters are given in Table 4. This particular choice of parameters is in agreement with [24].…”
Section: A1 Dimensionless Area Formulation—type I Spontaneous Curvasupporting
confidence: 89%
See 1 more Smart Citation
“…Note that W is a scalar multiple of the total elastic bending energy of the membrane and h ( α ) is a scalar multiple of the mean curvature at the corresponding points on the membrane. The boundary conditions used for the original unknowns are: The boundary conditions for the corresponding sensitivities are all set to be zero. Our choices for the input parameters are given in Table 4. This particular choice of parameters is in agreement with [24].…”
Section: A1 Dimensionless Area Formulation—type I Spontaneous Curvasupporting
confidence: 89%
“…Our choices for the input parameters are given in Table 4. This particular choice of parameters is in agreement with [24].…”
Section: A1 Dimensionless Area Formulation—type I Spontaneous Curvasupporting
confidence: 89%
“…Polymerization of actin filaments drives membrane protrusion; in parallel, membrane-associated proteins can also induce membrane curvature by the insertion of conical transmembrane proteins or hydrophobic protein domains into the membrane ( 66 , 67 ). Intriguingly, intrinsically disordered domains, when attached to membranes, can drive membrane protrusion either with a positive or negative curvature ( 68 70 ).…”
Section: Mechanisms For Inducing Membrane Curvature and Protein Enricmentioning
confidence: 99%
“…Many examples in biology display some of the phenomena we investigate here but with additional subtleties and complications. Recent studies have shown that condensates can induce membrane deformations in clathrin-mediated endocytosis (42) and in synthetic systems (43). While we expect that surface densities can substantially deform the membrane, and that deformations may influence the interactions between membrane and bulk, we don’t allow this in our model and so cannot explore it’s consequences here.…”
Section: Discussionmentioning
confidence: 99%